Enhance Micro, Small and Medium Enterprises’ financial performance - Aditya Amanda PANE (Academic Finance)
Purpose: This study aims to determine the factors that influence the increase in MSMEs income such as e-commerce, capital and business experience. The type of data used is primary data using a sample of 47 MSMEs located on Soekarno Hatta Street, Binjai City, Indonesia.